2014
DOI: 10.1101/gad.245621.114
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs control the apoptotic threshold in primed pluripotent stem cells through regulation of BIM

Abstract: Mammalian primed pluripotent stem cells have been shown to be highly susceptible to cell death stimuli due to their low apoptotic threshold, but how this threshold is regulated remains largely unknown. Here we identify microRNA (miRNA)-mediated regulation as a key mechanism controlling apoptosis in the post-implantation epiblast. Moreover, we found that three miRNA families, miR-20, miR-92, and miR-302, control the mitochondrial apoptotic machinery by fine-tuning the levels of expression of the proapoptotic pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
64
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(66 citation statements)
references
References 40 publications
1
64
1
Order By: Relevance
“…On the other hand, we did not detect any increase in Bim mRNA after exposure to ionizing radiation (Fig. 4C), in contrast to what was suggested by a previous study on mouse embryos (Pernaute et al, 2014). These discrepancies between in vitro and in vivo assays underline the multiplicity of mechanisms by which cells can opt in or out of survival/death control.…”
Section: Elevated Expression Of Noxa Bim and Bak Lowers The Apoptoticontrasting
confidence: 56%
See 1 more Smart Citation
“…On the other hand, we did not detect any increase in Bim mRNA after exposure to ionizing radiation (Fig. 4C), in contrast to what was suggested by a previous study on mouse embryos (Pernaute et al, 2014). These discrepancies between in vitro and in vivo assays underline the multiplicity of mechanisms by which cells can opt in or out of survival/death control.…”
Section: Elevated Expression Of Noxa Bim and Bak Lowers The Apoptoticontrasting
confidence: 56%
“…Depending on the cell context, the activation of p53 triggers arrest, repair, differentiation, senescence or apoptosis (Carvajal and Manfredi, 2013). Several studies performed in human embryonic stem cells (ESCs) or mouse peri-gastrulation embryos revealed that various mechanisms may prime stem cells for apoptosis, such as the presence of constitutively active Bax at the Golgi (Dumitru et al, 2012), an imbalance between pro-and antiapoptotic factors lowering the apoptotic threshold (Liu et al, 2013), or the control of Bim (Bcl2l11) expression by miRNAs, which would allow a fast release upon stress induction (Pernaute et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The specificity of the phenotypic defects observed in Foxd3 −/− cells was confirmed by performing experiments in which transient overexpression of Foxd3 in these cells significantly restored their differentiation potential (Figure S3D). The extensive cell death observed in Foxd3 −/− mESC upon EpiLC differentiation could indicate that, in addition to the silencing of naïve pluripotency genes, a major role of Foxd3 during this cellular transition could be to increase cell survival in primed pluripotent cells, which are characterized by a low apoptotic threshold (Pernaute et al, 2014). In agreement with this, Gene Ontology analysis of genes upregulated in Foxd3 −/− mESC revealed a significant overrepresentation of pro-apoptotic genes (Figure S3E).…”
Section: Resultsmentioning
confidence: 99%
“…This post-implantation developmental arrest could be the result of the abnormally high expression of two major groups of genes repressed by Foxd3: (i) naïve pluripotency and (ii) pro-apoptotic genes. Accumulating evidences suggest that primed pluripotent cells display hypersensitivity to cell death and a low apoptotic threshold (Heyer et al, 2000; Pernaute et al, 2014). Thus, future work should elucidate if repression of pro-apoptotic genes by Foxd3 represents an important requirement for the survival of primed pluripotent cells.…”
Section: Discussionmentioning
confidence: 99%
“…Mammalian BH3-only genes are also subject to post-transcriptional regulation via microRNAs (miRNAs). It has been demonstrated, for example, that the 3 ′ untranslated region (UTR) of Bim mRNA is the target of several miRNAs, which act to down-regulate and fine-tune Bim expression (Ventura et al 2008;Kole et al 2011;Qian et al 2011;Pernaute et al 2014; for review, see Sionov et al 2015).…”
mentioning
confidence: 99%